Comparison of Trace Element Levels of Lichen Species Living on Different Habitats - Yazici, Kenan; Aslan, Ali; Çiçek, Arzu (Asian Journal of Chemistry, 2011)
In this paper, concentrations of 18 trace elements, Al, B, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, S, Se, Si and Zn were determined by inductively coupled plasma-optical emission spectrometry (ICP-OES) in 16 lichen species living in four different habitats at 39 localities in Ardahan (Turkey). Cd, Na, Ni and Pb are the only available elements in some lichens living in some certain localities. Cd, Na, Ni and Pb are not necessary elements for the lichen metabolism, but the lichen species can take them into their bodies from their habitats or atmosphere (if there are) and store them even if it haven't got any role in the lichen metabolism. Moreover, some lichens living in some localities contain high concentrations (almost 177 folds of Fe: Ardahan- Hanak Altas: 1.13266 %), 104 folds of Ca (Posof, 2 km to Kursunçavus, mainroadside: 3.1066.6 %), 96 folds of Na (Ardahan-Hanak Altas: 0.090 %), 36 folds of Ni (Ardahan-Hanak Altas: 0.002386 %), 30 folds of Cr (Ardahan-Hanak Altas: 0.001853 %), 27 folds of Al (Ardahan, Göle 20 km to Ardahan mainroad side: 0.6960 %) and 22 folds of Mn (Ardahan-Hanak, Altas: 0.03946 %). The highest values of Al, Cr, Cu, K, Mn, Ni, P, S and Zn were determined in Dermatocarpon miniatum, while the highest values of Cd, Fe, Mg and Na were accumulated by Peltigera rufescens. On the other hand, the highest amounts of B and Se were accumulated by Peltigera canina, Ca by Rhizoplaca chrysoleuca and Pb by Parmelia sulcata.